2009
DOI: 10.1136/bjsm.2008.056150
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors for anterior cruciate ligament ruptures:COL1A1gene variant

Abstract: The TT genotype of the COL1A1 Sp1 binding site polymorphism was significantly under-represented in South African participants with ACL ruptures. We propose that this sequence variant be the first specific genetic element to be included in multifactorial models developed to understand the aetiology and risk factors for ACL rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
7
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(197 citation statements)
references
References 24 publications
(43 reference statements)
6
173
7
5
Order By: Relevance
“…The frequency of the 5A allele was 0.11 in the control group and 0.14 in the ACL group. This is similar to that in a population in Asia reported by Takahashi et al (2001) and Liu et al (2010), although different from those in South Africa reported by Posthumus et al (2009).…”
Section: Patient Characteristicssupporting
confidence: 77%
“…The frequency of the 5A allele was 0.11 in the control group and 0.14 in the ACL group. This is similar to that in a population in Asia reported by Takahashi et al (2001) and Liu et al (2010), although different from those in South Africa reported by Posthumus et al (2009).…”
Section: Patient Characteristicssupporting
confidence: 77%
“…All these studies indicate that there is a strong (more than 50%) genetic influence on the nature if injuries occurring. Other studies show that the presences of these variations in DNA are related to injuries produced in the connective tissue although most of these studies have been performed in non-sports population [10][11][12][13].…”
Section: Genetic Variation and Detection Methodsmentioning
confidence: 99%
“…Since the previous ACL retreat, a growing number of common DNA sequence variants within genes involved in various biological processes have been associated with susceptibility to ACL rupture. These include variants within several genes that encode collagens [169][170][171][172][173][174][175] and proteoglycans 176 involved in the formation of the collagen fibril, the basic building block of ligaments. A subset of these variants has been specifically associated with ACL ruptures in females but not in males.…”
Section: Genetic Risk Factorsmentioning
confidence: 99%